Clinical outcome of portal vein thrombosis in patients with digestive cancers: A large AGEO multicenter study. Issue 3 (March 2018) - Regnault, Hélène; Emambux, Sheik; Lecomte, Thierry; Doat, Solene; Dhooge, Marion; Besson, Marie; Dubreuil, Olivier; Moryoussef, Frederic; Silvain, Christine; Bachet, Jean-Baptiste; Tougeron, David
Abstract: Introduction: Management of portal vein thrombosis (PVT) in cancer patients remains discussed. Aims: The objective of this multicenter retrospective study was to investigate the management and outcome of PVT in patients with digestive cancers other than hepatocellular carcinoma (HCC). Method: Main inclusion criteria were trunk or branch PVT in patients with locally advanced or metastatic digestive cancers. Predictive factors of bleeding and overall survival (OS) were evaluated in univariate and multivariate analysis. Results: Between 2012 and 2016, 118 patients with PVT and digestive cancers were identified. The majority had a pancreatic cancer (50%). Sixty-six percent of patients had trunk PVT location. Endoscopic screening of portal hypertension was performed in only 7 patients (1%) and 5 had esophageal varices. Gastrointestinal bleeding occurred in 22 patients (19%) and 12 patient deaths (17%) were related to a gastrointestinal hemorrhage. Metastatic disease (HR = 2.83 [95%CI 1.47–5.43], p < 0.01) and gastrointestinal hemorrhage (HR = 1.68 [95%CI 1.01–2.78], p = 0.04) were associated with OS in multivariate analysis. Only trunk PVT location was significantly associated with gastrointestinal hemorrhage in multivariate analysis (HR = 5.56 [95%CI 1.18–26.32], p = 0.03). Conclusion: A high rate of variceal bleeding leading to death was found in this cohort. Endoscopic screening and the efficacy of prophylactic treatment of variceal bleeding remain to be evaluated in a prospective study.